Developmental changes in the reflectance spectra of temperate deciduous tree leaves and implications for thermal emissivity and leaf temperature. Issue 2 (29th November 2020) - Richardson, Andrew D.; Aubrecht, Donald M.; Basler, David; Hufkens, Koen; Muir, Christopher D.; Hanssen, Leonard
Summary: Leaf optical properties impact leaf energy balance and thus leaf temperature. The effect of leaf development on mid‐infrared (MIR) reflectance, and hence thermal emissivity, has not been investigated in detail. We measured a suite of morphological characteristics, as well as directional‐hemispherical reflectance from ultraviolet to thermal infrared wavelengths (250 nm to 20 µm) of leaves from five temperate deciduous tree species over the 8 wk following spring leaf emergence. By contrast to reflectance at shorter wavelengths, the shape and magnitude of MIR reflectance spectra changed markedly with development. MIR spectral differences among species became more pronounced and unique as leaves matured. Comparison of reflectance spectra of intact vs dried and ground leaves points to cuticular development – and not internal structural or biochemical changes – as the main driving factor. Accompanying the observed spectral changes was a drop in thermal emissivity from about 0.99 to 0.95 over the 8 wk following leaf emergence. Emissivity changes were not large enough to substantially influence leaf temperature, but they could potentially lead to a bias in radiometrically measured temperatures of up to 3 K. Our results also pointed to the potential for using MIR spectroscopy to better understand species‐level differences in cuticular development and composition.